Review paperOmalizumab in an allergology clinic: real life experience and future developments - Kupczyk, Maciej; Kuna, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Omalizumab is a recombinant humanized monoclonal antibody that reduces levels of circulating IgE and expression of IgE high affinity receptor (FCεRI) on mast cells and basophils. Its role in the therapy of allergic asthma and urticaria is well established. According to GINA guidelines, omalizumab should be considered as an important alternative to systemic corticosteroids in uncontrolled asthma. Several ongoing trials will evaluate omalizumab efficacy in the treatment of other allergic diseases and conditions. Further studies are needed to answer several practical questions on the optimal duration of treatment and possible biomarkers to predefine a cohort of responders to this therapy.